Comparative Assessment of Perception about Angle Inclination of Mandibular and Maxillary Incisors on the Cephalometric Analysis between Skeletal Class 3 and Orthognathic Cases - Ahmad Hija; Dror Michael Allon (Applied Sciences, 2022)
Before orthognathic surgery, a thorough diagnosis of the maxillofacial structure is performed for combined orthodontic–surgical treatment planning. One of the tools that are used for this collaboration is the cephalometric radiograph. Cephalometric analysis is a method for measuring the location of specific anatomical landmarks upon a cephalogram. Some of these parameters are more difficult to define accurately in cases of dentofacial deformities. Therefore, the data obtained from different examiners are characterized by high variability. The present study aimed to examine whether there is a significant variation in the physicians’ measurements between orthognathic Class I (normal) cases and the cases of skeletal deformity Class III. The study involved ten physicians with a mean age of 27. All physicians underwent appropriate instruction for reading and analyzing cephalometric radiographs, and all physicians were instructed about their role in the study. Each participant received 100 cephalometric radiographs, consisting of 50 radiographs of patients with a regular facial structure (Class-I = orthognathic) and 50 photographs of patients with a specific skeletal deformity (Class-III = prognathic). According to the Frankfort Horizontal plane, each physician marked the upper incisor (U1) longitudinal axis on the radiograph and the lower incisor (L1) longitudinal axis according to the mandibular plane. Then, we measured the angle degree with the Cephninja® application. Afterward, we performed a statistical analysis of the t-test with Bonferroni correction to check whether there is a significantly large standard deviation between the indices in the orthognathic cases compared to the prognathic cases. In the group of physicians who participated in this sample of these cephalometric radiographs, we found that in prognathic patients, the upper incisor angle measurements showed significantly more t variance relative to those physicians’ corresponding measurements radiographs of orthognathic patients. Variability increases as skeletal deformity become more severe (p = 0.026) in U1 TO FH and (p = 0.014) L1 TO MP. Cephalometric measurements, which are essential for the correct diagnosis and planning of combined orthodontic treatment, suffer from a significant examiner-based bias that is greater as deformity becomes more severe. This conclusion has implications for the accuracy of the model on which the entire plan process of the combined treatment of facial and jaw deformities is based. The surgeon should use CBCT (cone-beam computed tomography) for its three-dimensional superiority over cephalometric imaging, which will result in a more accurate evaluation of surgery planning and performance.